Mesoscale eddies in the subpolar North Atlantic: their ecological importance and conservation significance - Lea-Anne Henry; Jason Cleland; Anna Gebruk; René Schubert; Alice Della Penna; Peter Gaube; Christian Mohn; Brynn Devine; Arne Biastoch; Camille M.L.S. Pagniello; Keno Ferter; George Wolff; et al. (Progress in Oceanography, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Pelagic sharks target long‐lived, retentive anticyclonic eddies in the Northwest Atlantic Ocean - Camrin D. Braun; Peter Gaube; Alice Della Penna; Simon R. Thorrold; Laura H. McDonnell; G. Chris Fischer; Gonzalo Mucientes; Nuno Queiroz; Mahmood Shivji; David W. Sims; Gregory B. Skomal; Bradley Wetherbee; et al. (Limnology and Oceanography, 2025)
Open ocean ecosystems represent the largest habitat on Earth and are highly dynamic in time and space. Mesoscale eddies are a primary driver of this variability and serve a key structural role in ocean ecosystems. Eddies modulate marine biodiversity beyond their impacts on plankton, influencing many ecologically and commercially important predators that may preferentially occupy anticyclonic eddies. However, how animal‐eddy interactions scale across predator species and the mechanistic drivers of these relationships remain an area of active research. We integrated satellite tracking data for sharks with observations of mesoscale eddies to determine how four shark species interact with eddies in the Gulf Stream region. Based on over 24,000 tracking days, we found that blue, white, and shortfin mako sharks selected for the cores of anticyclones while the use of eddies by tiger sharks was less conspicuous. Some particularly large and long‐lived anticyclones were occupied by tagged sharks for multiple weeks suggesting that these eddies may serve as hotspots for pelagic predators.

Giants in the cold: Morphological evidence for vascular heat retention in the viscera but not the skeletal muscle of the basking shark ( Cetorhinus maximus ) - C. Antonia Klöcker; Axel Schlindwein; Martin C. Arostegui; Ingrid M. Bruvold; Joel V. Wernström; Montserrat Martin‐Armas; David W. Sims; Nicolas Straube; Andreas Altenburger; Claudia Junge (Journal of Fish Biology, 2025)
Fewer than 50 of the over 30,000 extant species of fishes have developed anatomical specializations facilitating endothermy in specific body regions. The plankton‐feeding basking shark ( Cetorhinus maximus ), traditionally classified as an ectotherm, was recently shown to have regionally endothermic traits such as centralized red muscle (RM) along its body trunk and elevated (white) muscle temperatures. However, key anatomical features essential for classification as a regional endotherm, such as the presence of vascular rete mirabile , could not be confirmed in this cold‐water giant. This study compared the morphology of heat‐generating and heat‐retaining tissues – associated with skeletal RM, the cranium and viscera – in the basking shark with those of a confirmed regional endotherm, the porbeagle ( Lamna nasus ), and a polar ectotherm, the Greenland shark ( Somniosus microcephalus ). Despite the presence of more medial RM in the basking shark's trunk, the absence of paired lateral vessels and a perfusing rete strongly suggests a lack of RM endothermy in this species. However, the presence of small arterial plexuses in the orbit, along with the discovery of visceral retia associated with the stomach, spleen and valvular intestine, in addition to distinct vascular arrangements in the liver and kidney, indicates potential for cranial and, particularly, visceral endothermy in C. maximus . These specializations, combined with reduced conductive heat loss from partial RM internalization and large body size, may enable C. maximus to maintain regionally elevated body temperatures, facilitating their active lifestyle also in cold‐water environments. Enhanced sensory perception and digestive efficiency may aid prey acquisition and processing in the dimly lit meso‐ and bathypelagic zones, as well as high‐latitude regions. Our findings provide initial insights into the thermal adaptations of these circum‐globally distributed, highly migratory ram filter feeders. Further research is needed to better understand the eco‐physiological implications of these adaptations, especially in the context of rapid ocean warming across their range, including Atlantification in the Arctic, and other anthropogenic pressures in the Anthropocene.

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

The vulnerability of sharks, skates, and rays to ocean deoxygenation: Physiological mechanisms, behavioral responses, and ecological impacts - Matt J. Waller; Nicolas E. Humphries; Freya C. Womersley; Alexandra Loveridge; Amy L. Jeffries; Yuuki Watanabe; Nicholas Payne; Jayson Semmens; Nuno Queiroz; Emily J. Southall; David W. Sims (Journal of Fish Biology, 2024)
Levels of dissolved oxygen in open ocean and coastal waters are decreasing (ocean deoxygenation), with poorly understood effects on marine megafauna. All of the more than 1000 species of elasmobranchs (sharks, skates, and rays) are obligate water breathers, with a variety of life‐history strategies and oxygen requirements. This review demonstrates that although many elasmobranchs typically avoid hypoxic water, they also appear capable of withstanding mild to moderate hypoxia with changes in activity, ventilatory responses, alterations to circulatory and hematological parameters, and morphological alterations to gill structures. However, such strategies may be insufficient to withstand severe, progressive, or prolonged hypoxia or anoxia where anaerobic metabolic pathways may be used for limited periods. As water temperatures increase with climate warming, ectothermic elasmobranchs will exhibit elevated metabolic rates and are likely to be less able to tolerate the effects of even mild hypoxia associated with deoxygenation. As a result, sustained hypoxic conditions in warmer coastal or surface‐pelagic waters are likely to lead to shifts in elasmobranch distributions. Mass mortalities of elasmobranchs linked directly to deoxygenation have only rarely been observed but are likely underreported. One key concern is how reductions in habitat volume as a result of expanding hypoxia resulting from deoxygenation will influence interactions between elasmobranchs and industrial fisheries. Catch per unit of effort of threatened pelagic sharks by longline fisheries, for instance, has been shown to be higher above oxygen minimum zones compared to adjacent, normoxic regions, and attributed to vertical habitat compression of sharks overlapping with increased fishing effort. How a compound stressor such as marine heatwaves alters vulnerability to deoxygenation remains an open question. With over a third of elasmobranch species listed as endangered, a priority for conservation and management now lies in understanding and mitigating ocean deoxygenation effects in addition to population declines already occurring from overfishing.

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Shark conservation requires mortality-limiting regulations amid global change - Neil Hammerschlag; David W. Sims (Trends in Ecology & Evolution, 2024)

Highly active fish in low oxygen environments: vertical movements and behavioural responses of bigeye and yellowfin tunas to oxygen minimum zones in the eastern Pacific Ocean - Nicolas E. Humphries; Daniel W. Fuller; Kurt M. Schaefer; David W. Sims (Marine Biology, 2024)
Oxygen minimum zones in the open ocean are predicted to significantly increase in volume over the coming decades as a result of anthropogenic climatic warming. The resulting reduction in dissolved oxygen (DO) in the pelagic realm is likely to have detrimental impacts on water-breathing organisms, particularly those with higher metabolic rates, such as billfish, tunas, and sharks. However, little is known about how free-living fish respond to low DO environments, and therefore, the effect increasing OMZs will have cannot be predicted reliably. Here, we compare the responses of two active predators (bigeye tuna Thunnus obesus and yellowfin tuna Thunnus albacares ) to DO at depth throughout the eastern Pacific Ocean. Using time-series data from 267 tagged tunas (59,910 days) and 3D maps of modelled DO, we find that yellowfin tuna respond to low DO at depth by spending more time in shallower, more oxygenated waters. By contrast, bigeye tuna, which forage at deeper depths well below the thermocline, show fewer changes in their use of the water column. However, we find that bigeye tuna increased the frequency of brief upward vertical excursions they performed by four times when DO at depth was lower, but with no concomitant significant difference in temperature, suggesting that this behaviour is driven in part by the need to re-oxygenate following time spent in hypoxic waters. These findings suggest that increasing OMZs will impact the behaviour of these commercially important species, and it is therefore likely that other water-breathing predators with higher metabolic rates will face similar pressures. A more comprehensive understanding of the effect of shoaling OMZs on pelagic fish vertical habitat use, which may increase their vulnerability to surface fisheries, will be important to obtain if these effects are to be mitigated by future management actions.

Context-dependent changes in maritime traffic activity during the first year of the COVID-19 pandemic - Alexandra Loveridge; Christopher D. Elvidge; David A. Kroodsma; Timothy D. White; Karen Evans; Akiko Kato; Yan Ropert-Coudert; Julia Sommerfeld; Akinori Takahashi; Robert Patchett; Benjamin Robira; Christian Rutz; et al. (Global Environmental Change, 2024)

Direct measurement of cruising and burst swimming speeds of the shortfin mako shark ( Isurus oxyrinchus ) with estimates of field metabolic rate - Matt J. Waller; Nuno Queiroz; Ivo da Costa; Tiago Cidade; Bruno Loureiro; Freya C. Womersley; Jorge Fontes; Pedro Afonso; Bruno C. L. Macena; Alexandra Loveridge; Nicolas E. Humphries; Emily J. Southall; et al. (Journal of Fish Biology, 2023)
The shortfin mako shark is a large‐bodied pursuit predator thought to be capable of the highest swimming speeds of any elasmobranch and potentially one of the highest energetic demands of any marine fish. Nonetheless, few direct speed measurements have been reported for this species. Here, animal‐borne bio‐loggers attached to two mako sharks were used to provide direct measurements of swimming speeds, kinematics and thermal physiology. Mean sustained (cruising) speed was 0.90 m s −1 (±0.07 s.d. ) with a mean tail‐beat frequency (TBF) of 0.51 Hz (±0.16 s.d. ). The maximum burst speed recorded was 5.02 m s −1 (TBF max = 3.65 Hz) from a 2 m long female. Burst swimming was sustained for 14 s (mean speed = 2.38 m s −1 ), leading to a 0.24°C increase in white muscle temperature in the 12.5 min after the burst. Routine field metabolic rate was estimated at 185.2 mg O 2 kg −1 h −1 (at 18°C ambient temperature). Gliding behaviour (zero TBF) was more frequently observed after periods of high activity, especially after capture when internal (white muscle) temperature approached 21°C (ambient temperature: 18.3°C), indicating gliding probably functions as an energy recovery mechanism and limits further metabolic heat production. The results show shortfin mako sharks generally cruise at speeds similar to other endothermic fish – but faster than ectothermic sharks – with the maximum recorded burst speed being among the highest so far directly measured among sharks, tunas and billfishes. This newly recorded high‐oxygen‐demand performance of mako sharks suggests it may be particularly vulnerable to habitat loss due to climate‐driven ocean deoxygenation.

Global tracking of shark movements, behaviour and ecology: A review of the renaissance years of satellite tagging studies, 2010–2020 - Samantha Renshaw; Neil Hammerschlag; Austin J. Gallagher; Nicolas Lubitz; David W. Sims (Journal of Experimental Marine Biology and Ecology, 2023)

Circles in the sea: annual courtship “torus” behaviour of basking sharks Cetorhinus maximus identified in the eastern North Atlantic Ocean - David W. Sims; Simon D. Berrow; Ken M. O'Sullivan; Nicholas J. Pfeiffer; Richard Collins; Kev L. Smith; Brianna M. Pfeiffer; Paul Connery; Shane Wasik; Lois Flounders; Nuno Queiroz; Nicolas E. Humphries; et al. (Journal of Fish Biology, 2022)
Groups of basking sharks engaged in circling behaviour are rarely observed, and their function remains enigmatic in the absence of detailed observations. Here, underwater and aerial video recordings of multiple circling groups of basking sharks during late summer (August and September 2016–2021) in the eastern North Atlantic Ocean showed groups numbering between 6 and 23 non‐feeding individuals of both sexes. Sharks swam slowly in a rotating “torus” (diameter range: 17–39 m), with individuals layered vertically from the surface to a maximum depth of 16 m. Within a torus, sharks engaged in close‐following, echelon, close‐flank approach or parallel‐swimming behaviours. Measured shark total body lengths were 5.4–9.5 m (mean L T : 7.3 m ± 0.9 s.d. ; median: 7.2 m, n = 27), overlapping known lengths of sexually mature males and females. Males possessed large claspers with abrasions that were also observed on female pectoral fins. Female body colouration was paler than that of males, similar to colour changes observed during courtship and mating in other shark species. Individuals associated with most other members rapidly (within minutes), indicating toroidal behaviours facilitate multiple interactions. Sharks interacted through fin–fin and fin–body contacts, rolling to expose the ventral surfaces to following sharks, and breaching behaviour. Toruses formed in late summer when feeding aggregations in zooplankton‐rich thermal fronts switched to non‐feeding following and circling behaviours. Collectively, the observations explain a courtship function for toruses. This study highlights northeast Atlantic coastal waters as a critical habitat supporting courtship reproductive behaviour of endangered basking sharks, the first such habitat identified for this species globally.

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Global-Scale Environmental Niche and Habitat of Blue Shark (Prionace glauca) by Size and Sex: A Pivotal Step to Improving Stock Management - Jean-Noël Druon; Steven Campana; Frederic Vandeperre; Fábio H. V. Hazin; Heather Bowlby; Rui Coelho; Nuno Queiroz; Fabrizio Serena; Francisco Abascal; Dimitrios Damalas; Michael Musyl; Jon Lopez; et al. (Frontiers in Marine Science, 2022)
Blue shark ( Prionace glauca ) is amongst the most abundant shark species in international trade, however this highly migratory species has little effective management and the need for spatio-temporal strategies increases, possibly involving the most vulnerable stage or sex classes. We combined 265,595 blue shark observations (capture or satellite tag) with environmental data to present the first global-scale analysis of species’ habitat preferences for five size and sex classes (small juveniles, large juvenile males and females, adult males and females). We leveraged the understanding of blue shark biotic environmental associations to develop two indicators of foraging location: productivity fronts in mesotrophic areas and mesopelagic micronekton in oligotrophic environments. Temperature (at surface and mixed layer depth plus 100 m) and sea surface height anomaly were used to exclude unsuitable abiotic environments. To capture the horizontal and vertical extent of thermal habitat for the blue shark, we defined the temperature niche relative to both sea surface temperature ( SST ) and the temperature 100 m below the mixed layer depth ( T mld+100 ). We show that the lifetime foraging niche incorporates highly diverse biotic and abiotic conditions: the blue shark tends to shift from mesotrophic and temperate surface waters during juvenile stages to more oligotrophic and warm surface waters for adults. However, low productivity limits all classes of blue shark habitat in the tropical western North Atlantic, and both low productivity and warm temperatures limit habitat in most of the equatorial Indian Ocean (except for the adult males) and tropical eastern Pacific. Large females tend to have greater habitat overlap with small juveniles than large males, more defined by temperature than productivity preferences. In particular, large juvenile females tend to extend their range into higher latitudes than large males, likely due to greater tolerance to relatively cold waters. Large juvenile and adult females also seem to avoid areas with intermediate SST (~21.7-24.0°C), resulting in separation from large males mostly in the tropical and temperate latitudes in the cold and warm seasons, respectively. The habitat requirements of sensitive size- and sex-specific stages to blue shark population dynamics are essential in management to improve conservation of this near-threatened species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Meta‐Fish‐Lib : A generalised, dynamic DNA reference library pipeline for metabarcoding of fishes - Rupert A. Collins; Giulia Trauzzi; Katherine M. Maltby; Thomas I. Gibson; Frances C. Ratcliffe; Jane Hallam; Sophie Rainbird; James Maclaine; Peter A. Henderson; David W. Sims; Stefano Mariani; Martin J. Genner (Journal of Fish Biology, 2021)
The accuracy and reliability of DNA metabarcoding analyses depend on the breadth and quality of the reference libraries that underpin them. However, there are limited options available to obtain and curate the huge volumes of sequence data that are available on public repositories such as NCBI and BOLD. Here, we provide a pipeline to download, clean and annotate mitochondrial DNA sequence data for a given list of fish species. Features of this pipeline include (a) support for multiple metabarcode markers; (b) searches on species synonyms and taxonomic name validation; (c) phylogeny assisted quality control for identification and removal of misannotated sequences; (d) automatically generated coverage reports for each new GenBank release update; and (e) citable, versioned DOIs. As an example we provide a ready‐to‐use curated reference library for the marine and freshwater fishes of the U.K. To augment this reference library for environmental DNA metabarcoding specifically, we generated 241 new MiFish‐12S sequences for 88 U.K. marine species, and make available new primer sets useful for sequencing these. This brings the coverage of common U.K. species for the MiFish‐12S fragment to 93%, opening new avenues for scaling up fish metabarcoding across wide spatial gradients. The Meta‐Fish‐Lib reference library and pipeline is hosted at https://github.com/genner-lab/meta-fish-lib .

Oceanic Diel Vertical Movement Patterns of Blue Sharks Vary With Water Temperature and Productivity to Change Vulnerability to Fishing - Marisa Vedor; Gonzalo Mucientes; Sofia Hernández-Chan; Rui Rosa; Nick Humphries; David W. Sims; Nuno Queiroz (Frontiers in Marine Science, 2021)
In the pelagic environment diel vertical movements (DVM) are widespread across taxa, from zooplankton ascending from day-time depths into surface layers at night to avoid visual predators, to apex predators following prey movements to maximise foraging opportunities. The drivers of DVM in large predators such as pelagic sharks have only recently begun to be investigated in detail with the advent of sophisticated archival tags and high-resolution oceanographic datasets. In this study, we satellite tagged adult [>180 cm fork length, (FL)] blue sharks ( Prionace glauca ) in the North Atlantic Ocean to examine behavioural changes in response to the encountered environment, and therefore, to determine potential risks of capture using pelagic longline fisheries data. Although blue sharks recurrently use surface waters, cyclic diel behaviours were observed, with >95% of night-time spent above 250 m depth and variable day-time depth use. Hence, three different diel behaviours were identified during the tracking period: (i) regular normal DVM (nDVM) (dawn descent – dusk ascent, with over 90% of nighttime spent above 250 m, and between 5 and 50% of the day below this threshold); (ii) surface-oriented behaviour (occupation of surface waters both day and night), and (iii) deep depth-oriented nDVM [dawn descent – dusk ascent, with the majority (>50%) of daytime spent at depth]. Importantly, diel behaviours generally occurred in different ocean regions with nDVM frequently observed in high latitudes, associated with cold, highly productive waters (e.g., North Atlantic Current/Labrador Current convergence zone, West African upwelling area), while depth-oriented nDVM was observed in warm, oligotrophic areas. Thus, day-time occupation of shallow waters significantly increased with lower water temperature at depth (100 m), and with increasing concentration (and decreasing depth) of the chlorophyll a maximum. During nights of full moon blue sharks spent significantly more time in the depth range of longline hooks, while fishing effort and catches were also higher. We demonstrate that increased occupancy of surface layers driven by highly productive, cold waters and greater lunar illumination lead to higher capture risk. Understanding habitat-specific vulnerability to fishing in a commercially important pelagic shark species is essential for improving management and conservation measures.

At the Turn of the Tide: Space Use and Habitat Partitioning in Two Sympatric Shark Species Is Driven by Tidal Phase - James S. E. Lea; Nicolas E. Humphries; Jenny Bortoluzzi; Ryan Daly; Rainer G. von Brandis; Ela Patel; Evan Patel; Christopher R. Clarke; David W. Sims (Frontiers in Marine Science, 2020)

Overhauling Ocean Spatial Planning to Improve Marine Megafauna Conservation - Ana Micaela Martins Sequeira; Graeme Clive Hays; David W. Sims; Víctor M. Eguíluz; Jorge P. Rodríguez; Michelle R. Heupel; Rob Harcourt; Hannah Calich; Nuno Queiroz; Daniel Paul Costa; Juan Fernández-Gracia; Luciana C. Ferreira; et al. (Frontiers in Marine Science, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Ty-6, a major begomovirus resistance gene on chromosome 10, is effective against Tomato yellow leaf curl virus and Tomato mottle virus - Upinder Gill; John W. Scott; Reza Shekasteband; Eben Ogundiwin; Cees Schuit; David M. Francis; Sung-Chur Sim; Hugh Smith; Samuel F. Hutton (Theoretical and Applied Genetics, 2019)

Management implications of highly resolved hierarchical population genetic structure in thinhorn sheep - Zijian Sim; Corey S. Davis; Bill Jex; Troy Hegel; David W. Coltman (Conservation Genetics, 2019)

Correction to: Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2019)

Convergent Foraging Tactics of Marine Predators with Different Feeding Strategies across Heterogeneous Ocean Environments - Nuno Queiroz; Catarina Vila-Pouca; Ana Couto; Emily J. Southall; Gonzalo Mucientes; Nicolas E. Humphries; David W. Sims (Frontiers in Marine Science, 2017)

Genome‐wide set of SNP s reveals evidence for two glacial refugia and admixture from postglacial recolonization in an alpine ungulate - Zijian Sim; Jocelyn C. Hall; Bill Jex; Troy M. Hegel; David W. Coltman (Molecular Ecology, 2016)
Past glaciation events have played a major role in shaping the genetic diversity and distribution of wild sheep in North America. The advancement of glaciers can isolate populations in ice‐free refugia, where they can survive until the recession of ice sheets. The major Beringian refugium is thought to have held thinhorn sheep ( Ovis dalli ) populations during times of glacial advance. While isolation in the major refugium can account for much of the genetic and morphological diversity seen in extant thinhorn sheep populations, mounting evidence suggests the persistence of populations in smaller minor refugia. We investigated the refugial origins of thinhorn sheep using ~10 000 SNP s obtained via a cross‐species application of the domestic sheep ovine HD BeadChip to genotype 52 thinhorn sheep and five bighorn sheep ( O. canadensis ) samples. Phylogenetic inference revealed a distinct lineage of thinhorn sheep inhabiting British Columbia, which is consistent with the survival of a group of thinhorn sheep in a minor refugium separate from the Beringian refugium. Isolation in separate glacial refugia probably mediated the evolution of the two thinhorn sheep subspecies, the white Dall's sheep ( O. d. dalli ), which persisted in Beringia, and the dark Stone's sheep ( O. d. stonei ), which utilized the minor refugium. We also found the first genetic evidence for admixture between sheep from different glacial refugia in south‐central Yukon as a consequence of post glacial expansion and recolonization. These results show that glaciation events can have a major role in the evolution of species inhabiting previously glaciated habitats and the need to look beyond established refugia when examining the evolutionary history of such species.

Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2016)
Skates and rays constitute the most speciose group of chondrichthyan fishes, yet are characterised by remarkable levels of morphological and ecological conservatism. They can be challenging to identify, which makes monitoring species compositions for fisheries management purposes problematic. Owing to their slow growth and low fecundity, skates are vulnerable to exploitation and species exhibiting endemism or limited ranges are considered to be the most at risk. The Madeira skate Raja maderensis is endemic and classified as ‘Data Deficient’ by the IUCN, yet its taxonomic distinctiveness from the morphologically similar and more wide-ranging thornback ray Raja clavata is unresolved. This study evaluated the sequence divergence of both the variable control region and cytochrome oxidase I ‘DNA barcode’ gene of the mitochondrial genome to elucidate the genetic differentiation of specimens identified as R. maderensis and R. clavata collected across much of their geographic ranges. Genetic evidence was insufficient to support the different species designations. However regardless of putative species identification, individuals occupying waters around the Azores and North African Seamounts represent an evolutionarily significant unit worthy of special consideration for conservation management.

Shark personalities? Repeatability of social network traits in a widely distributed predatory fish - David M. P. Jacoby; Lauren N. Fear; David W. Sims; Darren P. Croft (Behavioral Ecology and Sociobiology, 2014)

Loss of P2X7 nucleotide receptor function leads to abnormal fat distribution in mice - Kim L. Beaucage; Andrew Xiao; Steven I. Pollmann; Matthew W. Grol; Ryan J. Beach; David W. Holdsworth; Stephen M. Sims; Mark R. Darling; S. Jeffrey Dixon (Purinergic Signalling, 2014)

Seasonal abundance, philopatry and demographic structure of Caribbean reef shark (Carcharhinus perezi) assemblages in the north-east Exuma Sound, The Bahamas - Edward J. Brooks; David W. Sims; Andy J. Danylchuk; Katherine A. Sloman (Marine Biology, 2013)

Social behaviour in sharks and rays: analysis, patterns and implications for conservation - David M P Jacoby; Darren P Croft; David W Sims (Fish and Fisheries, 2012)
There are widespread records of grouping behaviour in both adult and juvenile sharks and rays (Class Chondrichthyes, Subclass Elasmobranchii). Yet despite burgeoning descriptions of these events, many of the proximate and ultimate causes of group living in these top predators remain elusive. Given the documented negative anthropogenic effects on many shark populations globally, there is an increasing need to understand how behaviourally mediated grouping influences population distributions and abundance, and the role this plays in exacerbating vulnerability to fishing mortality. Here, we analyse group living in elasmobranchs: we describe our current understanding of the patterns, mechanisms and functions of both aggregation (where grouping is not driven by social mechanisms) and social grouping (where grouping is influenced by social interaction) and discuss some of the current methods used to study social behaviour in this taxa. In particular, social preferences in elasmobranchs have received relatively little attention. We propose that the study of shark aggregations may benefit from a more fine‐scale analytical approach offered by detailed exploration of social interactions using social network analysis. Better understanding of the frequency and longevity of social relations, in conjunction with current long‐term data on habitat use and site philopatry, will likely serve for a more informed approach to coastal and pelagic elasmobranch conservation initiatives.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Characterisation of polymorphic microsatellite loci in the small-spotted catshark (Scyliorhinus canicula L.) - Andrew M. Griffiths; Didier Casane; Matthew McHugh; Victoria J. Wearmouth; David W. Sims; Martin J. Genner (Conservation Genetics Resources, 2011)

Levels of connectivity between longnose skate (Dipturus oxyrinchus) in the Mediterranean Sea and the north-eastern Atlantic Ocean - Andrew M. Griffiths; David W. Sims; Andrew Johnson; Arve Lynghammar; Matthew McHugh; Torkild Bakken; Martin J. Genner (Conservation Genetics, 2011)

The ability of a benthic elasmobranch to discriminate between biological and artificial electric fields - Joel A. Kimber; David W. Sims; Patricia H. Bellamy; Andrew B. Gill (Marine Biology, 2011)

The biology and ecology of the ocean sunfish Mola mola: a review of current knowledge and future research perspectives - Edward C. Pope; Graeme C. Hays; Tierney M. Thys; Thomas K. Doyle; David W. Sims; Nuno Queiroz; Victoria J. Hobson; Lukas Kubicek; Jonathan D. R. Houghton (Reviews in Fish Biology and Fisheries, 2010)

Identification of QTL associated with resistance to bacterial spot race T4 in tomato - Samuel F. Hutton; Jay W. Scott; Wencai Yang; Sung-Chur Sim; David M. Francis; Jeffrey B. Jones (Theoretical and Applied Genetics, 2010)

Characterisation of polymorphic microsatellite markers for skates (Elasmobranchii: Rajidae) from expressed sequence tags - Aliya El Nagar; Matthew McHugh; Toby Rapp; David W. Sims; Martin J. Genner (Conservation Genetics, 2010)

Body size‐dependent responses of a marine fish assemblage to climate change and fishing over a century‐long scale - MARTIN J. GENNER; DAVID W. SIMS; ALAN J. SOUTHWARD; GEORGINA C. BUDD; PATRICIA MASTERSON; MATTHEW MCHUGH; PETER RENDLE; EMILY J. SOUTHALL; VICTORIA J. WEARMOUTH; STEPHEN J. HAWKINS (Global Change Biology, 2010)
Commercial fishing and climate change have influenced the composition of marine fish assemblages worldwide, but we require a better understanding of their relative influence on long‐term changes in species abundance and body‐size distributions. In this study, we investigated long‐term (1911–2007) variability within a demersal fish assemblage in the western English Channel. The region has been subject to commercial fisheries throughout most of the past century, and has undergone interannual changes in sea temperature of over 2.0 °C. We focussed on a core 30 species that comprised 99% of total individuals sampled in the assemblage. Analyses showed that temporal trends in the abundance of smaller multispecies size classes followed thermal regime changes, but that there were persistent declines in abundance of larger size classes. Consistent with these results, larger‐growing individual species had the greatest declines in body size, and the most constant declines in abundance, while abundance changes of smaller‐growing species were more closely linked to preceding sea temperatures. Together these analyses are suggestive of dichotomous size‐dependent responses of species to long‐term climate change and commercial fishing over a century scale. Small species had rapid responses to the prevailing thermal environment, suggesting their life history traits predisposed populations to respond quickly to changing climates. Larger species declined in abundance and size, reflecting expectations from sustained size‐selective overharvesting. These results demonstrate the importance of considering species traits when developing indicators of human and climatic impacts on marine fauna.

The role of learning in shark behaviour - Tristan L Guttridge; Arthur A Myrberg; Ila F Porcher; David W Sims; Jens Krause (Fish and Fisheries, 2009)
The role of learning in behaviour is well known for many animal taxa, including teleost fishes, insects, birds and mammals. However, its importance to sharks in everyday behavioural processes has rarely been considered. Almost 50 years ago the first learning experiments on sharks were conducted; our first section discusses these studies and places them in a framework of associative and non‐associative learning. These experiments showed that sharks were capable of different forms of learning, such as operant and classical conditioning and habituation. Sharks could learn associations as rapidly as other vertebrates and also remember training regimes for several months. However, much of this experimental evidence was based on small sample sizes and few shark orders, such as Carcharhiniformes and Orectobliformes, leaving large gaps in our knowledge of the general learning capabilities of other shark orders. We also examine recent research that has tested for, or inferred learning in behavioural processes. This section reveals that sharks, like teleost fishes use learning to improve prey search and capture to potentially navigate and orientate in their home range and recognize conspecifics, heterospecifics and mates. Learning is also discussed in relation to ecotourism and fisheries. Findings indicated that these activities may lead to conditioning of sharks and that considerable effort should go into investigating what impact this could have on the shark species involved. Finally, we discuss the importance of combining laboratory experiments with field studies, the use of new experimental techniques, the role of model species and research priorities for future work.

Concordance of genetic and fin photo identification in the great white shark, Carcharodon carcharias, off Mossel Bay, South Africa - Chrysoula Gubili; Ryan Johnson; Enrico Gennari; W. Hermann Oosthuizen; Deon Kotze; Mike Meÿer; David W. Sims; Catherine S. Jones; Leslie Robert Noble (Marine Biology, 2009)

The effects of climate variability on zooplankton and basking shark ( Cetorhinus maximus ) relative abundance off southwest Britain - PETER A. COTTON; DAVID W. SIMS; SAM FANSHAWE; MARK CHADWICK (Fisheries Oceanography, 2005)
At small spatial scales basking sharks ( Cetorhinus maximus ) forage selectively on zooplankton along thermal fronts, but the factors influencing broader scale patterns in their abundance and distribution remain largely unknown. Using long‐term sightings data collected off southwest Britain between 1988 and 2001, we show that the number of basking sharks recorded was highly correlated with abiotic factors, principally sea surface temperature (SST) and the lagged effect of SST in the previous month, but only very weakly to zooplankton density. This suggests that the changes in number of basking sharks recorded over large spatio‐temporal scales are more closely related to the availability of climate‐driven thermal resources than prey availability, whereas the converse is supported by previous studies at local scales. Taken together, these results imply scale‐dependent behavioural responses in basking sharks, with small‐scale foraging movements linked by broad scale responses to temperature variation.

Congruent trends in long‐term zooplankton decline in the north‐east Atlantic and basking shark ( Cetorhinus maximus ) fishery catches off west Ireland - David W. Sims; Philip C. Reid (Fisheries Oceanography, 2002)
Trends in basking shark ( Cetorhinus maximus ) fishery catches off Achill Island, west Ireland between 1949 and 1975 were examined in relation to zooplankton (total copepod) abundance in four adjacent sea areas over a 27‐year period. The numbers of basking sharks caught and copepod abundance showed downward trends and were positively correlated ( r ‐value range, 0.44–0.74). A possible explanation for the downward trend in shark catches was that progressively fewer basking sharks occurred there between 1956 and 1975 because fewer copepods, their food resource, occurred near the surface off west Ireland over the same period. We suggest that the decline in basking sharks may have been due to a distributional shift of sharks to more productive areas, rather than a highly philopatric, localized stock that was over‐exploited.

Comparison of the Effects of Wet N Deposition (NH4Cl) and Dry N Deposition (NH3) on UK Moorland Species - Ian D. Leith; Lucy J. Sheppard; Carole E.R. Pitcairn; J. Neil Cape; Paul W. Hill; Valerie H. Kennedy; Y. Sim Tang; Ron I. Smith; David Fowler (Water, Air, & Soil Pollution, 2001)